1999
DOI: 10.1063/1.125452
|View full text |Cite
|
Sign up to set email alerts
|

High-density transition layer in oxynitride interfaces on Si(100)

Abstract: Articles you may be interested inAn atomic model of the nitrous-oxide-nitrided SiO 2 / Si interface

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Based on our XRR results we also found that a 1-2 nm interfacial layer with a density of ∼2.5-2.9 g cm −3 was also formed at the SRON-SiO 2 interlayer interface. High-density interfacial layers have also been observed in the XRR curves of nitrided SiO 2 thin film on Si wafers [33]. We also observed in these XRR results that the thickness of the film annealed at 850 • C decreased by ∼16%, and the density of the annealed film increased by ∼14%.…”
Section: Discussionsupporting
confidence: 73%
“…Based on our XRR results we also found that a 1-2 nm interfacial layer with a density of ∼2.5-2.9 g cm −3 was also formed at the SRON-SiO 2 interlayer interface. High-density interfacial layers have also been observed in the XRR curves of nitrided SiO 2 thin film on Si wafers [33]. We also observed in these XRR results that the thickness of the film annealed at 850 • C decreased by ∼16%, and the density of the annealed film increased by ∼14%.…”
Section: Discussionsupporting
confidence: 73%